Biological Evaluation Of Herbal Preparations And Formulation Standardization: A Literature Study - Kumar, Mohit; Sharma, Amit; Juneja, Rinka; Parashar, Tarun; Arif, Mohammad; Dev Singh, Aniruddh; Kumar, Ashok (Journal of Neonatal Surgery, 2025)
The use of herbal medicines has gained significant attention in recent years due to their potential therapeutic benefits and minimal side effects. However, the lack of standardization in herbal preparation and formulation has raised concerns about their safety and efficacy. This literature study aims to evaluate the biological activity of various herbal preparations and highlight the importance of formulation standardization. The study extensively reviews the literature on the biological evaluation of herbal preparations, including the assessment of phytochemical composition, antioxidant activity, anti-inflammatory properties, and cytotoxicity. Additionally, the study discusses the current challenges in standardizing herbal formulations, including the variability in plant material, extraction methods, and manufacturing processes. The study concludes that the biological activity of herbal preparations depends on several factors, including the selection of plant material, preparation method, and formulation standardization. Therefore, standardized protocols for the preparation and formulation of herbal medicines are essential to ensure their safety, efficacy, and reproducibility.